The Life Cycle of the Bacterial-Feeding Nematode Diplolaimella stagnosa and Its Population Growth in Response to Temperature and Food Availability - Zhao, Jingchao; Zhang, Jun; Zhu, Xueli; Lu, Jianbo; Jin, Binsong; Chen, Huili (Frontiers in Ecology and Evolution, 2022)
Diplolaimella is a ubiquitous cosmopolitan genus, but information on the life cycles of its species is limited. Here, we describe the life cycle of a free-living bacterivorous nematode, Diplolaimella stagnosa, and report the effects of temperature and food availability on its population dynamics. Specimens were primarily collected from the intertidal zone of Hangzhou Bay Wetland, China and culture experiments were conducted in nutrient agar media with habitat water at 20°C. The nematode primarily fed on an unidentified bacterium that it carried. Under these conditions, both males and females matured in 16 days. Reproduction was by gamogenesis and gravid females normally carried 7–8 eggs. Embryogenesis was completed in 58 h, and the entire life cycle (egg to adult) was completed in 16–18 days. During juvenile development, body lengths of worms increased linearly up to the 16th day, and then remained constant. Body lengths of males and females were 898.1±6.0 µm and 1039.7±14.7 µm, respectively. Nematodes kept at 25°C had a greater population increase than those at 20°C, and the population growth of nematodes was substantially higher in microcosms with abundant bacteria supplied by leaves of Phragmites australis than in microcosms without plant litter. Based on its life strategy and the influence of food availability and temperature on population growth, D. stagnosa was allocated to group c-p 2, suggesting its potential use as a model organism in toxicological studies.